Application of microsatellite dna markers for genetic diversity analysis in wild and domesticated stock of macrobrachium rosenbergii / Nurriza Ab. Latif - Ab. Latif, Nurriza (2011)
Ten microsatellite loci (Mbr-1, Mbr-3, Mbr-4, Mbr-5, Mbr-7, Mbr-8, Mbr-10a, Mbr-10b, UVC-807 and UVC-817) were used to assess the genetic diversity and makeup of different populations of Macrobrachium rosenbergii in Malaysia. A total of 120 individuals from four hatcheries and 116 individuals from four wild populations were studied. The samples were Sarawak River (SRWK), Terengganu River (TRGN), Timun River (NSBL), Kedah River (KDH), Thailand (THAI), National Prawn Fry Production and Research Centre (NAPFRE), Mun‟s Aquaculture (HatA) and Wong‟s Aquaculture (HatB). Allele sizes of all samples were scored using the ABI 3100 Genetic Analyzer. A total of 161 alleles were detected at 10 loci across the eight populations. All domesticated and wild populations demonstrated relatively high genetic variation with an average of 9.00 to 13.10 alleles per locus (A) and observed heterozygosities (Ho) ranging from 0.5833 to 0.8000. All the studied populations deviated from Hardy–Weinberg equilibrium proportions at a number of loci. Genetic distance computed by Nei (1978) denotes that the shortest genetic distance was between KDH and NSBL (D=0.2087) while the greatest was between HatA and NAPFRE (D=0.9333). Analysis of molecular variance (AMOVA) revealed significant differentiations in all populations with moderate FST values of between 0.0311 and 0.1438. Phylogenetic analysis depicted a close genetic relationship of M. rosenbergii between HatB and NSBL while samples from HatA diverged and was not clustered with any populations though the three populations originated from the same area. Microsatellites analysis revealed high levels of genetic variation and genetic differentiation among all the populations tested. Regular monitoring on genetic diversity and structure of M. rosenbergii is needed for genetic improvement and management programmes.